2010
DOI: 10.1128/aem.00148-10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution in Tissue and Seasonal Variation of Norovirus Genogroup I and II Ligands in Oysters

Abstract: Bivalve molluscan shellfish, such as oysters, filter large volumes of water as part of their feeding activities and are able to accumulate and concentrate different types of pathogens, particularly noroviruses, from fecal human pollution. Based on our previous observation of a specific binding of the Norwalk strain (prototype norovirus genogroup I) to the oyster digestive tract through an A-like carbohydrate structure indistinguishable from human blood group A antigen and on the large diversity between strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 56 publications
8
90
1
Order By: Relevance
“…SENG-6 are the binding sites of NoVLPs. The A antigen has also been found in HBGA-like substances in the digestive tissues of oysters (32), and the critical role of the terminal N-acetyl-galactosamine residue in the strain-dependent accumulation of HuNoVs in oysters has been discussed previously (29,30). Bacterial A-like substances can also affect the genotype-dependent fate of HuNoVs in the environment because each HuNoV genotype has its own HBGA binding profile (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SENG-6 are the binding sites of NoVLPs. The A antigen has also been found in HBGA-like substances in the digestive tissues of oysters (32), and the critical role of the terminal N-acetyl-galactosamine residue in the strain-dependent accumulation of HuNoVs in oysters has been discussed previously (29,30). Bacterial A-like substances can also affect the genotype-dependent fate of HuNoVs in the environment because each HuNoV genotype has its own HBGA binding profile (12).…”
Section: Resultsmentioning
confidence: 99%
“…While GII.4 NoVLPs bound to S. epidermidis ATCC 35984 ( Fig. 2A), it was previously shown that this genotype recognizes a broad range of ligands other than HBGAs, such as those containing sialic acid (29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…It is currently demonstrated that NoV particles bind to glycan ligands, some being very similar to human histo-blood group antigen-like (HBGA) carbohydrates in the digestive tissue of shellfish and may account for the inefficiency of depuration practices (Le Guyader et al, 2006b;Maalouf et al, 2010b).…”
Section: Efficacy Of Decontamination Methods On Fresh Producementioning
confidence: 99%
“…In this case NoV monitoring by PCR provided an effective assessment of virus risk and permitted effective risk management controls to be implemented. However some specific binding may influence these results depending on the strains and the shellfish species (Maalouf et al, 2010b;Zakhour et al, 2010). The use of PCR for monitoring virus risk is now the main focus for development of more effective control measures internationally.…”
Section: Evaluation Of the Efficacy Of Current Preventive Measures Inmentioning
confidence: 99%
“…(Le Guyader et al, 2006;Mcleod et al, 2009aMcleod et al, , 2009bTian et al, 2006;Wang et al, 2008), (Maalouf et al, 2010;Nappier et al, 2008). Provost et al (2011) (hematocytes) (acidic digestion) .…”
Section: Real Time Rt-pcrmentioning
confidence: 99%